Hearing device use and tinnitus retraining therapy for clients with tinnitus: assessing the benefits in a private practice in Johannesburg, South Africa - Swart, Duone Rochelle (My University, 2018)
Background: Hearing devices have been used as a tool for treating tinnitus since the 1940's. In the same way, tinnitus retraining therapy (TRT) has been used to treat tinnitus originating from various causes successfully. A variety of research focuses on each of the above-mentioned treatment options, but few researched the combination of these two treatment methods. In addition, no current research exists for a South African population, relating to the benefits of these treatments used together. Purpose: To assess the benefits of treating tinnitus using a combination of tinnitus retraining therapy and hearing devices, using the tinnitus handicap inventory (THI). To identify themes within the 25 THI items and how they affect the daily functioning of the client experiencing tinnitus. Methods: A quantitative, non-experimental, cross-sectional design was used for this research study. The research sample included 29 clients, who were fitted with hearing devices and received accompanying tinnitus retraining therapy. Clients were seen in private practice settings in Johannesburg, South Africa. Clients were seen by TRT trained audiologists. Clients completed the THI after each TRT visit. Descriptive statistics and a statistical z-test was used to analyse the scores obtained from the THls. Thematic analysis was used to analyse 25 THI items. Ethical clearance was obtained to conduct the study before data collection commenced. Results: The findings of this research showed that n=10 clients received 3-6 THI and hearing device therapy sessions. For these participants, a combination of TRT and hearing device use was successful in treating their tinnitus. The mean score for the first THI was 50,55 and the mean score for the last THI was 29,31. Statistical z-test results showed a statistically significant different between the first and last THI scores and supported the null hypothesis. Analysis of the 25 items of the THI showed that quality of life experienced by the client is adversely affected by tinnitus. Conclusion: The results for this study indicated that to receive benefit from a combination of TRT and hearing device use, the client must attend at least 3-6 consecutive TRT and hearing device sessions. TRT and hearing device use therapy should be provided within a team setting. Tinnitus influences the functional activities of the client, closely followed by influences on their emotional state.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Audiology to the Faculty of Humanities, School of Human and Community Development University of the Witwatersrand, Johannesburg, 2018